Frequency Of Hyponatremia In Children Admitted To The Pediatric Intensive Care Unit In A Tertiary-Care Hospital: A Cross-Sectional Study - Khan, Ammar Yasir; Idris, Arooba; Shabbir , Asad; Rashid, Sobia; Danish, Asad Iqbal; Qudrat, Syeda Mamoona (Journal of Rawalpindi Medical College, 2024)
Objective: Hyponatremia is relatively common in children with acute diarrhoea, occurring in around 10-15% of cases. This study aimed to determine the prevalence of hyponatremia in children with acute diarrhoea. Methods: A facility-based cross-sectional study was conducted at the Department of Pediatrics, Benazir Bhutto Hospital, Rawalpindi from April 2023 to September 2023. A total of 335 pediatric patients of both genders, aged up to 5 years, who were presented with acute diarrhoea and admitted to the pediatric intensive care unit (PICU) were enrolled in the study. Each child was assessed by taking a detailed history from the mother/caregiver regarding the frequency and duration of diarrhoea of the patient. A blood sample for serum electrolyte (Na) was taken under aseptic measures and was sent to the hospital’s laboratory. Patients were labelled as having hyponatraemia or normal serum sodium and results were confirmed by a consultant pathologist. Appropriate entries were made in the structured study proforma. Data were analyzed using SPSS version 22. Statistical significance was set at p < 0.05. Results: In this study, out of 335 cases, 28.96% (n=97) were between 0-2 years of age whereas 71.04% (n=238) were between 3-5 years of age. Mean±SD was calculated as 3.29±1.40 years, 69.25% (n=232) were male and 30.75% (n=103) were females. The frequency of hyponatremia in children with acute diarrhoea was recorded in 4.18% (n=14) whereas 95.82% (n=321) had no findings of morbidity. Conclusion: This study concluded that the frequency of hyponatremia in children with acute diarrhoea is not very high, however, other national and international studies are varied and need early management of this morbidity.